2007
DOI: 10.1037/0278-6133.26.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of psychological interventions for chronic low back pain.

Abstract: The purpose of this meta-analysis of randomized controlled trials was to evaluate the efficacy of psychological interventions for adults with noncancerous chronic low back pain (CLBP). The authors updated and expanded upon prior meta-analyses by using broad definitions of CLBP and psychological intervention, a broad data search strategy, and state-of-the-art data analysis techniques. All relevant controlled clinical trials meeting the inclusion criteria were identified primarily through a computer-aided litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
427
2
28

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 739 publications
(485 citation statements)
references
References 57 publications
21
427
2
28
Order By: Relevance
“…Several authors suggested that a complete understanding of clinical outcomes requires consideration of physical, psychological, and social factors [14,24]. Perruccio et al [20] noted that mental well-being is critical for understanding the relationship between physical health and selfrated health.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors suggested that a complete understanding of clinical outcomes requires consideration of physical, psychological, and social factors [14,24]. Perruccio et al [20] noted that mental well-being is critical for understanding the relationship between physical health and selfrated health.…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive-behavioural treatment is known to be one of the most effective interventions for this condition [2], although the effect sizes are only moderate.…”
Section: Introductionmentioning
confidence: 99%
“…However, evidence is inadequate for long-term efficacy and somewhat contradictory for effects on vocationally relevant outcomes. 35,36,40 Mechanisms involved in successful psychological treatments have received some attention. For example, Turner et al 41 found that mediators of improvement in pain and activity 1 year after CBT were cognitive variables, including patients' perceptions of control, disability, self-efficacy, harm, catastrophizing, and rumination.…”
Section: Efficacy Of Psychological Treatmentsmentioning
confidence: 99%
“…Since that initial publication, investigators have reported a large number of clinical trials evaluating the efficacy of various psychological treatment approaches and modalities, including CBT, biofeedback, and hypnosis, for a range of chronic pain diagnoses. 35,36 These studies focused primarily on patients with musculoskeletal disorders or heterogeneous samples of chronic pain; the percentage of patients with neuropathic pain was unspecified.…”
Section: Efficacy Of Psychological Treatmentsmentioning
confidence: 99%